ISMS: Integrated Safety Management System - Faidzli, Anastazry; Marjudi, Suziyanti (Applied Information Technology And Computer Science, 2024)
This study proposes the development and implementation of a web-based Integrated Safety Management System (ISMS). The proposed system can be used by industry that deals with hazards, risk or any other activities that can cause injury or harm. The system will also encompass some analytic tools such as incident reports, near misses and monthly safety analysis which can help the organization assess their construction site safety level. The case study for this project was conducted at the construction site located in Kuala Lumpur. The organization is currently facing operational challenges at one of their construction site. The core issue is their reliance on a conventional paper-based system for safety data management, which is further compounded by the small size of the on-site office, making efficient storage of essential safety documents, mandated for retention over a three-year period, quite challenging. Retrieving past documents for updates or compliance is also problematic. For the development of the proposed system, the Agile Model is selected as the system development methodology. It prioritizes continuous improvement based on customer feedback and adaptability to evolving requirements. During the system's implementation phase, the Laravel framework was used for the backend and TailwindCSS and JavaScript for the frontend. The result is a successful web-based Integrated Safety Management System (ISMS), effectively mitigating the challenges faced at construction site, significantly enhancing safety data management processes.